2005
DOI: 10.1261/rna.2207206
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Trf4p- and Trf5p-dependent polyadenylation to the processing and degradative functions of the yeast nuclear exosome

Abstract: The nuclear exosome is involved in a large number of RNA processing and surveillance pathways. RNase III cleavage intermediates destined to be 3¢-processed or degraded can be detected when the Rrp6p subunit of the nuclear exosome is absent. Here we show that these processing and degradation intermediates are polyadenylated, and that their polyadenylation is dependent on the activity of Trf4p and Trf5p, two variant poly(A) polymerases. Polyadenylation of cleavage intermediates was inhibited when Trf4p was absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 22 publications
5
98
0
Order By: Relevance
“…These data suggest that, depending on the gene context, snoRNA terminators possess the potential to direct polyadenylation. Previous data, indeed, reported polyadenylation of some sn/ snoRNAs precursors in an exosome-defective yeast strain (van Hoof et al 2000;Egecioglu et al 2006). Accordingly, a strain deleted for RRP6 showed that one to four adenines are present at the 39-end of C/D-box snoRNA precursors that had been incompletely processed (Grzechnik and Kufel 2008).…”
Section: The Nrd1 Complexmentioning
confidence: 82%
See 1 more Smart Citation
“…These data suggest that, depending on the gene context, snoRNA terminators possess the potential to direct polyadenylation. Previous data, indeed, reported polyadenylation of some sn/ snoRNAs precursors in an exosome-defective yeast strain (van Hoof et al 2000;Egecioglu et al 2006). Accordingly, a strain deleted for RRP6 showed that one to four adenines are present at the 39-end of C/D-box snoRNA precursors that had been incompletely processed (Grzechnik and Kufel 2008).…”
Section: The Nrd1 Complexmentioning
confidence: 82%
“…In yeast, noncanonical nuclear PAPs, Trf4/5 (Haracska et al 2005;Egecioglu et al 2006;, function in a nuclear RNA surveillance pathway as part of the TRAMP (Trf-Air-Mtr4 polyadenylation) complex, which activates degradation by the exosome of a variety of aberrant nuclear precursors of many types of RNAs after addition of a poly(A) tail (LaCava et al 2005). Although not well studied, this RNA surveillance function is likely conserved in humans since homologs of the TRAMP and exosome complexes are present in mammals.…”
Section: -End Processing Machinerymentioning
confidence: 99%
“…In addition to targeting unstable pre-tRNAs for decay, TRAMP is involved in the decay of a mutant U6 snRNA, several precursors to rRNAs and snRNAs, and transcripts of intergenic regions (LaCava et al 2005;Wyers et al 2005;Kadaba et al 2006). Yeast also contain a related poly(A) polymerase complex, consisting of the Trf4p-related protein Trf5p, Air1p, and Mtr4p, that has overlapping functions with the TRAMP complex (Egecioglu et al 2006;Houseley and Tollervey 2006;Kadaba et al 2006).…”
Section: Similar Pathways For Noncoding Rna Quality Control In Bactermentioning
confidence: 99%
“…Critically, budding yeast-derived TRAMP4 complex or recombinant Trf4-Air1/2 complex exclusively polyadenylates hypomodified tRNA i Met , suggesting that the TRAMP4 complex recognizes the structure/folding of an RNA substrate (22). Besides aberrant tRNAs, Trf4 also polyadenylates and stimulates the degradation of snRNAs, snoRNAs, rRNAs, and CUT RNAs, including the prototypic CUT, NEL025c (14,21,32,33).…”
mentioning
confidence: 99%